Sosialisasi Kelengkapan Administrasi Kesehatan dan Keselamatan Kerja (K3) pada Pekerja Proyek Bangunan - Marchamah, Dwi Nur Siti; Nisa, Choyrun (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Ivet, 2022)
Work accidents are accidents that occur related to work, including diseases that arise due to work relations, as well as accidents that occur on the way to and from work. The purpose of this community service is to increase the understanding of building project workers to be able to participate in BPJS Ketenagakerjaan. So that it can support the optimization program for the implementation of the Employment Social Security Program launched by the Government. The method of community service is carried out by counseling, discussion, and mentoring. As for the results of the service, it was obtained that counseling and mentoring accompanied by discussions of building project workers CV. Griya Rencana in Karanganyar Regency, has a positive impact on understanding and awareness of the completeness of occupational health and safety (K3) administration.